Hemodynamic Perturbations in Deep Brain Stimulation Surgery: First Detailed Description - Chowdhury, Tumul; Wilkinson, Marshall; Cappellani, Ronald B. (Frontiers in Neuroscience, 2017)
Background Hemodynamic perturbations can be anticipated in deep brain stimulation (DBS) surgery and may be attributed to multiple factors. Acute changes in hemodynamics may produce rare but severe complications such as intracranial bleeding, transient ischemic stroke and myocardium infarction. Therefore, this retrospective study attempts to determine the incidence of hemodynamic perturbances (rate) and related risk factors in patients undergoing deep brain stimulation surgery. Material and Methods After institutional approval, all patients undergoing DBS surgery for the past ten years were recruited for this study. Demographic characteristics, procedural characteristics and intraoperative hemodynamic changes were noted. Event rate was calculated and the effect of all the variables on hemodynamic perturbations was analyzed by regression model. Results Total hemodynamic adverse events during DBS surgery was 10.8 (0-42) and treated in 57 % of cases. Conclusion Among all the perioperative variables, the baseline blood pressure including systolic, diastolic and mean arterial pressure was found to have highly significant effect on these intraoperative hemodynamic perturbations.